(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2018)
Abstract Islam Education (PAI) at schools has not achieved the optimum level, due to the shortage of the PAI teacher. The number of the PAI teacher in Nusa Tenggara Barat (NTB) Province is currently not comparable with the number of students, because: (i) the impact of moratorium policy of the PAI teacher’s recruitment (pengangkatan guru), (ii) the teachers are retiring, and (iii) unscattered number of the PAI teacher. This research used qualitative method, supported by quantitative data. Data collection was conducted through observation, questionnaire, interview, and documentary. Meanwhile, data processing method was editing, coding, tabulating, and interpretation through qualitative and descriptive analysis. Research found that: 1) The shortage of the PAI teachers in NTB, for level SD (Elementary School), SMP (Junior High School), SMA (Senior High School), and SMK (Vocational High School); 2) The Ministry of Religious Affairs - District/City is facing the problem to organize the PAI teacher at schools, due to the recruitment and payroll system of the Education Board (Dinas Pendidikan); 3) The deployment of the PAI teacher has not followed the system of surplus and shortage analysis, based on education unit within the number of study groups; 4) The PAI teacher’s supervision at schools through Teachers Working Group (Kelompok Kerja Guru, KKG) and Lesson-Teacher Meeting (Musyawarah Guru Mata Pelajaran, MGMP). This research recommends that: 1) The demand of the PAI teacher at schools can be fulfilled by recruiting temporary teacher (guru honorer), done by schools and Education Board, by giving additional teaching duties for the PAI teacher who has not achieved minimum 24 hours; 2) The PAI teacher’s recruitment, deployment and supervision have to be fully authorized by The Ministry of Religious Affairs; 3) The surplus and shortage analysis of the PAI teacher is needed in Level Education Board (Dinas Pendidikan), The Ministry of Religious Affairs – District/City, and Education unit, and 4) The Ministry of Religious Affairs through Directorate of Islam Education (Direktorat Pendidikan Agama Islam) should allocate operational budget for proper KKG/MGMP actitivities of PAI. Abstrak Penyelenggaraan Pendidikan Agama Islam (PAI) di sekolah belum optimal karena kurangnya jumlah guru pendidikan agama Islam. Jumlah guru pendidikan agama Islam di provinsi Nusa Tenggara Barat saat ini tidak sebanding dengan jumlah siswa sebagai akibat kebijakan moratorium pengangkatan guru PAI, ada yang pensiun dan tidak meratanya sebaran guru PAI. Metode penelitian ini adalah kualitatif yang didukung oleh data kuantitatif. Pengumpulan data melalui teknik observasi, angket, wawancara dan dokumenter. Adapun teknik pengolahan data yang digunakan adalah editing, coding, tabulating dan interpretation data dengan menggunakan analisis deskriptif kualitatif. Temuan penelitian: 1) Jumlah guru PAI di provinsi Nusa Tenggara Barat pada jenjang SD, SMP, SMA dan SMK masih mengalami kekurangan; 2) Kementerian Agama Kabupaten/Kota mengalami kesulitan dalam mengkoordinasikan guru PAI di sekolah karena pengangkatan dan penggajian oleh Dinas Pendidikan; 3) Penempatan guru PAI belum berdasarkan kepada sistem analisis kelebihan dan kekurangan guru PAI berdasarkan satuan pendidikan sesuai jumlah rombongan belajar; 4) Pembinaan guru PAI di sekolah melalui Kelompok Kerja Guru (KKG) dan Musyawarah Guru Mata Pelajaran (MGMP). Penelitian ini merekomendasikan: 1) Pemenuhan guru PAI di sekolah dapat dilakukan melalui pengangkatan guru honorer oleh sekolah dan melalui Dinas Pendidikan, dengan memberikan tugas tambahan mengajar bagi guru PAI yang belum memenuhi jumlah minimal 24 jam; 2) Pengangkatan, penempatan dan pembinaan guru PAI seharusnya menjadi kewenangan penuh Kementerian Agama; 3) Perlunya sistem analisis kelebihan dan kekurangan guru PAI di tingkat Dinas Pendidikan, Kementerian Agama Kabupaten/Kota dan Satuan Pendidikan dan 4) Kementerian Agama melalui Direktorat Pendidikan Agama Islam perlu menganggarkan dana operasional kegiatan KKG/MGMP PAI yang memadai.